Sensing and configuring the world with text: bringing neo-Vygotskian thinking into dialogue with more-than-human literacies in early childhood. Issue 2 (4th March 2023) - Rodriguez Leon, Lucy
ABSTRACT: Research framed by evolving sociocultural theories have been fundamental in advancing the study of early childhood literacies. More recently the field has been enriched by posthumanist theories that have shifted the analytic gaze from children's participation in literacy practices and events, to the fluid relationality of literacies. Concurrently, neo-Vygotskian scholars have advanced cultural-historical concepts to study a child and their environment in unity. This paper brings neo-Vygotskian thinking into dialogue with 'more-than-human' literacies in early childhood. Drawing on vignettes generated from an ethnography involving 3–4-year-old children, the paper explores the in-between-ness of young children and the socio-material environment during encounters with text, to seek insights into the emerging idiosyncratic, subjectively, and relationally produced experiences. From this conceptual space, the paper considers the ways in which children's intention and orientation emerge with text and how micromoments in relations can be sites of potential transformation.